Edukasi Gizi Seimbang Sebagai upaya Pencegahan Stunting oleh KKN Universitas Palangka Raya di Desa Batuah Kecamatan Basarang Kabupaten Kapuas - Dewi Rakhmawati; Ahmad Rizqullah; Muhammad Yasin; Ananda Marpaung; Agustina Siagan; Shintike Debora Br Bangun; Nopa Lia Tiara; Ririn Kabes; Angel Agustin Saragih; Indra Setiawan; Givan Asselt Hatagalung; Karmi Itasni; Sonia Wulandari; Wirna Wirna; Johan Sriada Damanik (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
Stunting is a condition of impaired growth in children under five years of age due to chronic malnutrition, resulting in slower growth compared to their peers. Based on the Special Index Report on Stunting Management in Central Kalimantan Province for 2021-2022, it shows that almost every city and district has reached the index threshold but is indicated to be low or the index numbers are close to the lower limit. The IKPS (Special Stunting Management Index) for Kapuas Regency in 2021 reached 51.7 with a lower limit index of 47.0, categorized as poor, and in 2022 it only reached 49.2 with a lower limit index of 43.9, also categorized as poor. The KKN group designed several educational and nutritional intervention programs to increase community awareness and understanding of the importance of adequate and balanced nutritional intake. These programs include socialization about healthy eating patterns, counseling on the importance of nutrition for pregnant and breastfeeding mothers, and the provision of healthy corn pudding. The output of this activity is demonstrated by the increased knowledge of participants about the importance of adequate nutrition.